Evaluating the Effectiveness of Regional Asset Management Policies: A Case Study of Central Buton Regency - Rahmawati; Faizu, Abdul Hatab; Ramadhan, Syahril (Ilomata International Journal of Social Science, 2025)
This study aims to evaluate the effectiveness of the Regional Asset Management policy in the Central Buton Regency Government by focusing on the Matland Policy Implementation Model, which includes policy accuracy, implementation accuracy, target accuracy and environmental accuracy. The research method used is qualitative with data collection techniques through interviews, observations, and documentation. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the study show several important findings. First, positive policy accuracy, with Central Buton Regional Regulation Number 5 of 2018 formulated to overcome problems and support governance. Second, target accuracy is achieved, with appropriate interventions and low ambiguity, increasing the chances of successful implementation. Regional Asset Management Officials show a good response and readiness to implement the policy. Third, environmental accuracy shows positive dynamics through interactions between institutions and community involvement. Fourth, implementation accuracy is still not effective, as seen from the limited combination between the government and the community/private sector and the lack of privatization and the absence of contracting out. In addition, there are problems such as uncertified land and the low number of information boards. In conclusion, the accuracy of policies, accuracy of targets, and accuracy of the environment have been effective, but the accuracy of implementation has not been effective.